DESIGNING ENTREPRENEURIAL ORGANIZATIONAL MODEL BASED ON RESISTIVE ECONOMY IN THE MINISTRY OF EDUCATION OF IRAN (CASE STUDY OF WESTERN PROVINCES OF IRAN) - Gohari, Neda; Salajeghe, Sanjar (Revista Inclusiones, 2019)
This study aimed at designing an entrepreneurial organizational model based on the resistive economy in the ministry of education Iran. It was an applied developmental survey study using a questionnaire. In this research, factors associated with implementation were extracted from series of papers and interviews. Among them, 3 factors and 33 indicators which were more comprehensive were selected and the initial model was given to experts as a a survey with open questions. Delphi method confirmed all the factors. In the Delphi stage, the statistical population included 18 senior managers of the Ministry of Education in Lorestan province with organizational posts of the Director General, Deputy Director General, Senior Experts, Provincial Management of University of Farhangian of Lorestan Province, experts of the University of Farhangian and the two Parliament members. The validity of the model was checked using 183 managers of ministry of education and senior experts in 11 western cities. Using Kochren formula, the sample size was 370. The information analysis method was structural equation modeling in the AMOS software. The results confirmed the proposed model.